Digital Quiz as Media to Review Material for English Education Students - Dyah Mukaromah; Anisa Mutoharoh (Script Journal: Journal of Linguistics and English Teaching, 2019)
Abstract: This study aims to explain the digital quiz to review learning material. Material Development is a subject that is reviewed by the student and the review done through Quizalize. A digital quiz which is so user friendly and quick interesting. The participants of this research are sixteen students of English Education Department, from University of Technology Yogyakarta. The researchers used qualitative descriptive to analyze the data. Qualitative data are obtained from quiz that has been completed by the students. The result of this study shows that the display of the quiz is interesting, Quizalize provides analysis for each questions, Quizalize also shows the result for each student, grouped students into categories based on their score. The researchers recommend Quizalize as digital quiz that can be used by the teacher to review the material.Keywords: digital quiz, review, material development, quizalize